2023
DOI: 10.3389/fped.2023.1083962
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic assessment in children after cardiac surgery: A pilot study on the value of infrared thermography

Abstract: IntroductionLow cardiac output syndrome in the postoperative period after cardiac surgery leads to an increase in tissue oxygen extraction, assessed by the oxygen extraction ratio. Measurement of the oxygen extraction ratio requires blood gases to be taken. However, the temperature of the skin and various parts of the body is a direct result of blood flow distribution and can be monitored using infrared thermography. Thus, we conducted a prospective clinical study to evaluate the correlation between the therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The proportion of studies with a low-risk rating for concerns around the applicability of their findings in the patient selection, index test and reference standard domains were 73, 57 and 77%, respectively. Ten studies scored low risk ratings across all domains ( 11 , 12 , 18 , 20 , 24 , 25 , 27 , 30 , 36 , 39 ). One scored high-risk ratings across all domains ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of studies with a low-risk rating for concerns around the applicability of their findings in the patient selection, index test and reference standard domains were 73, 57 and 77%, respectively. Ten studies scored low risk ratings across all domains ( 11 , 12 , 18 , 20 , 24 , 25 , 27 , 30 , 36 , 39 ). One scored high-risk ratings across all domains ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of authors identified their studies as exploratory or assessing feasibility ( n = 16) ( 11 , 12 , 14–16 , 19 , 21 , 22 , 26 , 27 , 31 , 32 , 34 , 35 , 37 , 39 ). Few were described as validation or diagnostic accuracy studies ( n = 8) ( 13 , 17 , 18 , 20 , 24 , 33 , 36 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of studies with a low-risk rating for concerns around the applicability of their findings in the patient selection, index test and reference standard domains were 73, 57 and 77%, respectively. Ten studies scored low risk ratings across all domains (11,12,18,20,24,25,27,30,36,39). One scored high-risk ratings across all domains (16).…”
Section: Quality Appraisalmentioning
confidence: 99%
“…The use of an internal control enables individual basal temperature variations to be accounted for. In studies investigating core to peripheral temperature gradients, commonly the central temperature measurement used was taken from the internal canthus (15,18,30,37,39). This is based on international guidance (2).…”
Section: Measured Variablesmentioning
confidence: 99%
See 1 more Smart Citation